O23.3 Predictors of Self-Assessed Risk of Chlamydia Trachomatis Infection Among Adolescents in Norway. (13th July 2013) - Gravningen, K; Schirmer, H; Furberg, A; Simonsen, G S; Wilsgaard, T
Abstract : Background: Adolescents commonly underestimate their own risk of chlamydia infections. We aimed to examine the association between chlamydia prevalence and perceived risk of infection, and the predictors of perceived risk, among 15–20 year old adolescents in Norway. Methods: This population based cross-sectional study among students in 5 high schools included a web-questionnaire and Chlamydia trachomatis PCR in first-void urine (participation rate 85%, girls 800/boys 818, mean age 17.2 years). Perceived infection risk was assessed using a 5-point scale: 1 = none, 2 = low, 3 = medium, 4 = high, 5 = very high. Multivariable logistic regression analysis was applied using stepwise variable selection with 5% significance level and binary outcome: 'high' (3–5) versus 'low' (1–2) risk. Results: Chlamydia prevalence according to risk level was: none 3.6%, low 4.4%, medium 8.2%, and high/very high 16.4%. 28 of the 58 infected participants perceived their risk to be none/low. In the multivariable model, following factors were associated with high perceived risk: ≥ 2 sexual partners past 6 months (odds ratio (OR) 3.6), number of lifetime partners 1–2 (reference), 3–5 (OR 2.7), or ≥ 6 (OR 3.7), previous treatment (OR 2.2), clinical symptoms (OR 1.9), no steady relationship (OR 1.8), first intercourse without condom (OR 1.5), and younger age (OR 0.78 per year). Significant interaction was present between gender and substance use ( p = 0.004). Higher levels of substance use increased self-assessed risk only among boys. Among participants with low use, boys assessed risk higher than girls (OR 2.7). Among medium use participants, boys assessed risk lower than girls (OR 0.6). Among 665 participants perceiving none/low risk, both the 28 persons infected and a significant proportion of the non-infected scored on multiple chlamydia risk factors. Conclusions: Chlamydia prevalence increased with increasing perceived risk level. Mostly well-known chlamydia risk factors were significant in modelling risk perceptions. Adolescents need knowledge to more accurately assess their susceptibility to chlamydia infections.